Augmenting training–learning experience by design: a conceptual framework. Issue 1 (11th February 2020) - Shree, Sonal
Abstract : Purpose: The purpose of this paper is to explore the possibility of designing training sessions on the basis of a dramatic structure and inclusion of contextual narrative for facilitating transfer of learning. The role of stimulating curiosity in this process has also been scanned under the lens of neurobiological insights. Design/methodology/approach: The paper theoretically develops a framework through an integrative literature review to examine the prospect of enhanced learner engagement through structure, narrative and some interdisciplinary theories, namely, the gap theory of curiosity and the peak end theory. Findings: A contextual story-based training method designed on the basis of a dramatic plot structure can leverage on the learners' emotions for engaging learning sessions and retention of content. Such design offers potential to improvise and strengthen the overall training module design and delivery mechanism. The outcome is seen through enhanced peak moments of curiosity and satisfaction, thus enriching the overall training–learning process. Research limitations/implications: The study is theory based and non-empirical which does not give it a ground to make generalised statements and conclusions. This factor, however, paves the way for future research in the allied areas such as empirical testing of the framework by identifying and testing the variables and other contextual and causal factors. Practical implications: The suggested framework has practical implications for Learning and Development managers as well as academies. The conceptual framework provided in this work can lend some unique insights towards strengthening the training–learning process. Originality/value: Although the concept of using stories for training is not new, this study contributes by proposing a new theoretical framework that examines together the elements of sound dramatic structure and a story-based training method. Such a design, conceived by taking into account an understanding of the working mind, can influence the overall experience of achieving positive training–learning results.